2018
DOI: 10.1038/s41598-018-34868-9
|View full text |Cite
|
Sign up to set email alerts
|

Genetic effects of BDKRB2 and KNG1 on deep venous thrombosis after orthopedic surgery and the potential mediator

Abstract: Deep venous thrombosis (DVT) is a common complication of orthopedic surgery. Genetic risk factors and high heritability carried a substantial risk of DVT. In this study, we aimed to investigate the potential association in the Han Chinese population between the polymorphisms of BDKRB2 and KNG1 and DVT after orthopedic surgery (DVTAOS). A total of 3,010 study subjects comprising 892 DVT cases and 2,118 controls were included in the study, and 39 single nucleotide polymorphisms (SNPs) in total (30 for BDKRB2 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…Although previously identified in a candidate gene experiment as a risk factor for thrombosis 38 and suggestively associated in other GWAS for VTE, 39 this work represents the first time that the KNG1 locus, with lead variant rs710446, has been significantly associated to risk of VTE and FVIII in GWAS. rs710446 is a missense variant in the KNG1 gene that causes an amino acid change at the position 581 (Ile581Thr) 40 . Colocalization results between VTE and FVIII (CPC > 0.8) suggest that rs710446 in KNG1 gene is associated both with FVIII and VTE (Figure 4B).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Although previously identified in a candidate gene experiment as a risk factor for thrombosis 38 and suggestively associated in other GWAS for VTE, 39 this work represents the first time that the KNG1 locus, with lead variant rs710446, has been significantly associated to risk of VTE and FVIII in GWAS. rs710446 is a missense variant in the KNG1 gene that causes an amino acid change at the position 581 (Ile581Thr) 40 . Colocalization results between VTE and FVIII (CPC > 0.8) suggest that rs710446 in KNG1 gene is associated both with FVIII and VTE (Figure 4B).…”
Section: Resultsmentioning
confidence: 99%
“…There is strong biological evidence that associate KNG1 gene with the coagulation system 40,46,47 . HMWK, along with FXII and prekallikrein (PK) complex, conform the plasma kallikrein‐kinin system (KKS), that plays an important role in human physiology.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[8] Bradykinin receptor B2 (BDKRB2) encodes a G-protein coupled receptor of bradykinin (BK). [12] Accumulating reports have confirmed that BDKRB2 is capable of regulating calcium signaling. Through binding to BDKRB2, BK allows calcium to enter, leads to calcium-induced calcium release and evokes calcium signaling via upregulating the expression of transient receptor potential melastatin 7 (TRPM7).…”
Section: Introductionmentioning
confidence: 99%